Deterring cheating using a complex assessment design: A case study - Sonja Bjelobaba (Literacy Trek, 2021)
Attempts to translate written examinations normally conducted in a lecture hall to an online environment during emergency remote learning in response to COVID-19 have not proved entirely successful, and have led to a sharp increase in cases of suspected misconduct. This paper describes a case study which gives insights on the relationship between assessment design and academic integrity: Is it possible to deter students from cheating by means of assessment design? Previous research does promote certain assessment types, but also indicates that there is no single assessment type that students think is impossible to cheat on. The solution proposed in this paper is therefore to add complexity to the mixture. An alternative complex assessment design comprising several steps is introduced and exemplified by an assessment procedure piloted in a grammar course for preservice language teachers in mother tongue tuition. The design promotes academic integrity, signature pedagogy, student-centred learning, and collaboration within a community of practice in an online setting.